Outcome and prognostic value of N‐terminal pro‐brain natriuretic peptide and high‐sensitivity C‐reactive protein in mildly dilated cardiomyopathy vs. dilated cardiomyopathy - Jiayu Feng; Pengchao Tian; Lin Liang; Yuyi Chen; Yunhong Wang; Mei Zhai; Yan Huang; Qiong Zhou; Xuemei Zhao; Lang Zhao; Boping Huang; Liyan Huang; et al. (ESC Heart Failure)
Abstract Aims Mildly dilated cardiomyopathy (MDCM) was characterized as a subset of dilated cardiomyopathy (DCM) with systolic dysfunction and modest ventricular dilatation, of which the prognostic studies were limited. We aimed to compare the prognostic value of the N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) and high‐sensitivity C‐reactive protein (hs‐CRP) between MDCM and DCM. Methods and results We retrospectively included hospitalized patients diagnosed with DCM and a left ventricular ejection fraction ≤ 50% at Fuwai Hospital from 2006 to 2017. MDCM was defined as left ventricular end‐diastolic diameter index (LVEDDi) ≤ 33 mm/m2 in males and ≤34 mm/m2 in females. A total of 640 patients (median age 49 years, 24.8% female) were included in this study. At baseline, 110 cases (17%) were categorized as MDCM and 529 cases (83%) as DCM. Of 282 patients who had follow‐up echocardiograms ≥ 6 months, 7 MDCM patients (11.1%) evolved to DCM and 70 DCM patients (32.0%) recovered to MDCM by the change of LVEDDi. Compared with DCM, patients with baseline MDCM had lower composite risks of all‐cause mortality, heart transplantation, and heart failure rehospitalization [adjusted hazard ratio (HR) 0.63, 95% confidence interval (CI) 0.43–0.93, P = 0.019]. Both hs‐CRP and NT‐proBNP were independently associated with the composite endpoint in the overall cohort (hs‐CRP: adjusted HR 1.07, 95% CI 1.00–1.15, P = 0.036; NT‐proBNP: adjusted HR 1.11, 95% CI 1.02–1.22, P = 0.019). After a propensity‐score matching between MDCM and DCM, higher NT‐proBNP (above the median) was significantly associated with the outcome in DCM patients (HR 1.83, 95% CI 1.05–3.20, P = 0.034), but not in MDCM patients (HR 1.54, 95% CI 0.76–3.11, P = 0.227). On the contrary, higher hs‐CRP (above the median) showed prognostic value for adverse events in MDCM patients (HR 3.19, 95% CI 1.52–6.66, P = 0.002), but not in DCM patients (HR 1.04, 95% CI 0.61–1.79, P = 0.88). Conclusions In patients with MDCM, although no evidence suggested the prognostic role of NT‐proBNP, higher level of hs‐CRP was associated with outcome, supporting the use of hs‐CRP in risk stratification for patients with MDCM.